IGF1-R signals through the RON receptor to mediate pancreatic cancer cell migration - Jaquish, D.W.; Yu, P.T.; Shields, D.J.; French, R.P.; Maruyama, K.P.; Niessen, S.; Hoover, H.; Hoover, H.; Cravatt, B.; Lowy, A.M.
The RON receptor tyrosine kinase (RTK)is overexpressed in the majority of pancreatic cancers, yet its role in pancreatic cancer cell biology remains to be clarified. Recent work in childhood sarcoma identified RON as a mediator of resistance to insulin-like growth factor receptor (IGF1-R)-directed therapy. To better understand RON function in pancreatic cancer cells, we sought to identify novel RON interactants. Using multidimensional protein identification analysis, IGF-1R was identified and confirmed to interact with RON in pancreatic cancer cell lines. IGF-1 induces rapid phosphorylation of RON, but RON signaling did not activate IGF-1R indicating unidirectional signaling between these RTKs. We next demonstrate that IGF-1 induces pancreatic cancer cell migration that is RON dependent, as inhibition of RON signaling by either shRNA-mediated RON knockdown or by a RON kinase inhibitor abrogated IGF-1 induced wound closure in a scratch assay. In pancreatic cancer cells, unlike childhood sarcoma, STAT-3, rather than RPS6, is activated in response to IGF-1, in a RON-dependent manner. The current study defines a novel interaction between RON and IGF-1R and taken together, these two studies demonstrate that RON is an important mediator of IGF1-R signaling and that this finding is consistent in both human epithelial and mesenchymal cancers. These findings demand additional investigation to determine if IGF-1R independent RON activation is associated with resistanceto IGF-1R-directed therapies in vivo and to identify suitable biomarkers of activated RON signaling.